2022
DOI: 10.1101/2022.05.16.492158
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Differential Evasion of Delta and Omicron Immunity and Enhanced Fusogenicity of SARS-CoV-2 Omicron BA.4/5 and BA.2.12.1 Subvariants

Abstract: SummaryThe rising case numbers of the SARS-CoV-2 Omicron BA.4, BA.5, and BA.2.12.1 subvariants has generated serious concern about the course of the pandemic. Here we examine the neutralization resistance, infectivity, processing, and fusogenicity of spike from the BA.4/5 and BA.2.12.1 SARS-CoV-2 variants compared with other Omicron subvariants and Delta. Critically, we found that the new Omicron subvariants BA.4/5 and BA.2.12.1 were more resistant to neutralization by mRNA-vaccinated and boosted health care w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
28
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 45 publications
4
28
1
Order By: Relevance
“…Here, the largest fold decreases for neutralization against BA.4 were seen for unvaccinated individuals previously infected with Delta and BA.1 (23). For Delta, this is in contrast to a previous report, where Delta-wave patient sera neutralized not only Delta but also the BA.4/5 and BA.2.12.1 variants, which, like Delta, contain substitutions at position L452 (25). In our cohort, we noted that autologous titers to the Delta spike were higher than those in D614G and Beta, perhaps a consequence of the high viral loads that are associated with Delta infections (27).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Here, the largest fold decreases for neutralization against BA.4 were seen for unvaccinated individuals previously infected with Delta and BA.1 (23). For Delta, this is in contrast to a previous report, where Delta-wave patient sera neutralized not only Delta but also the BA.4/5 and BA.2.12.1 variants, which, like Delta, contain substitutions at position L452 (25). In our cohort, we noted that autologous titers to the Delta spike were higher than those in D614G and Beta, perhaps a consequence of the high viral loads that are associated with Delta infections (27).…”
Section: Discussioncontrasting
confidence: 99%
“…The ability of BA.4 to escape neutralization elicited by vaccination and previous infection is now well described (4,14,2225). Here, we have extended these studies to define BA.4 resistance to neutralizing and ADCC-mediating antibodies triggered by each of the four VOCs (D614G, Beta, Delta and BA.1) that sequentially caused waves of infection in South Africa (26).…”
Section: Discussionmentioning
confidence: 99%
“…Seventeen studies analyzed the efficacy of CCP and VaxCCP against Omicron sublineages other than BA.1 (summarized in Table 2 ). Those studieslargely confirmed that Omicron CCP per se is poorly effective against the cognate or other Omicron sublineages 22 (with the lone exception of cross-reactions among lineages sharing L452 mutations 23 and broad-spectrum nAbs elicited by BA.5 24 ). On the contrary, both homologous and heterologous efficacy of Omicron VaxCCP is again universally preserved 15 , 25 .…”
Section: Resultsmentioning
confidence: 73%
“…The Omicron strains, such as BA.1, BA.4, and BA.5, have remarkable growth advantages over ancestral VOCs, such as Beta, Delta, etc., featured by over 30 mutations in spike protein and 15 mutations in its receptor-binding domain (RBD). The newly characteristic mutation at the L452 site in BA.2.12.1 and BA.4, BA.5 lineages has resulted in further immune evasion and elevated transmissibility [ 1 ]. The primary series of approved vaccines based on a prototype SARS-CoV-2 exhibited remarkably reduced protective efficacy against Omicron compared to the parental virus strain, as suggested by the recent reports on neutralization capacity [ 2 , 3 , 4 ] and real-world vaccine effectiveness against symptomatic disease [ 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%